Pengaruh Pengawasan .danPemberdayaan terhadapPerilaku Karyawan Dalam Pelayanan Perijinan Pada Dinas Perindustrian dan Perdagangan Kota Medan - Sitorus, Monang (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2004)
The objective research and    analysis influence controlling and empowering to employees behavior in serivice permit  in board of industry and trade to  Board  of  Industry  and  Trade of  Medan  City.  The grand    theory controlling  testing writer by Robbins and Coulter (2005), empowering testing writer by Clutterbuck dan Kernaghan (2003)  and theory employees behavior testing writer by Marat (1981). The use of methodology eksplanatori survey and all responden is sensus. The data were analyzed by using  Path Analysis. The infuence the controlling  (X1)      to employees behavior (Y) indirect and direct is 23.8%;  lnfuence empowering (X2)    to employees behavior (Y) is 15.9%.   The effect controlling (X1)  and  empowering (X2)  to employees behavior  (Y)  is 39. 7%, and the residue 60. 3% influenced the other dissimilar factor (epsilon).